Anesthetic management of a child with previous history of malignant hyperthermia: case report [Malign hipertermi öyküsü olan çocuk olguda genel anestezi yönetimi] - (:unkn) unknown (My University, 2008)
Malignant hyperthermia is an uncommon life-threatening genetic sensitivity of skeletal muscles to volatile anesthetics and depolarizing neuromuscular relaxants triggered by anesthesia and is followed by an increase in temperature that may be fatal without prompt treatment. Here, we present our anesthetic management of a 6-year-old girl with previous history of malignant hyperthermia experience for the ventriculoatrial shunting.
Keywords: Child; General anesthesia; Malignant hyperthermia; Remifentanil; Rocuronium